(untitled) (Forest and Society, 2025)
Indonesia is a global hotspot of pitcher plant diversity with 80 Nepenthes species recorded to date - 59 protected under Indonesian law - and more species likely to be discovered and described in the future. Under Indonesian law, these protected Nepenthes can only be traded if they originate from artificially propagated sources, and trade necessitates specific permits and government-issued certification. The present study aimed to evaluate the trade of Nepenthes species protected by Indonesian law in Indonesian-language online markets. The trade data was searched in March 2024 in the top five most visited e-commerce in Indonesia, i.e., Shopee, Tokopedia, Lazada, Blibli, and Bukalapak. We discovered that 37 Nepenthes species (29 endemic to Indonesia; 14 species globally threatened) under protection in Indonesia were sold online, with 501 advertisements from 296 sellers. The majority (89.2%) of these sellers operated from Java Island. Our research documented the sale of 2,552 Nepenthes plants, totaling IDR 56,660,000 (USD 3,480). Additionally, sellers reported having 536,757 plants in stock, potentially worth over IDR 92 billion (USD 5,664,000). None of the sellers had permits for the Nepenthes they sold, indicating that they sold them illegally. Therefore, despite being designated as protected species in name, they lack effective protection in practice. The number of traded Nepenthes recorded in our study was higher than that reported by CITES (157 plants) over a 49-year period. Among the traded species, N. clipeata and N. sumatrana are two Critically Endangered species in the top 10 most advertised. These findings could aid the Indonesian Ministry of Environment and Forestry in identifying key players and regions involved in the trade, as well as assist conservationists and policymakers in determining which species need strong protection measures.